OVERVIEW OF THE STATE OF KNOWLEDGE ON PALEOTECTONIC STRESSES AND THEIR IMPLICATIONS FOR SOLUTION OF GEOLOGICAL PROBLEMS - L. A. Sim (Геодинамика и тектонофизика, 2015)
The most informative geological indicators of tectonic stress are faults on all scales and minor structural forms, such as dikes, mineralized veins, shear fractures, cleavage, slikenlines on slip planes of any genesis, foliation, cleavage, stilolite joints, hinges and axial planes of folds and flexures, etc. These indicators are analysed by various field tectonophysical methods developed in different countries. The article gives an overview of the history of the most widely used methods of tectonophysical paleotectonic stress reconstructions for geological structures of various scales. Reviewed are results of regional tectonophysical studies aimed at mapping paleotectonic stress and solution of possible mechanisms of formation of the structures located mainly in the territory of Russia and CIS countries. Special attention is given to application of results of the tectonic stress studies for solution of practical problems.